The value of primary colposcopy in genitourinary medicine–a six year review. Issue 3 (June 1994) - Moss, T R; Hawkswell, J; Fogarty, B; Dadswell, C
Abstract : OBJECTIVE–To evaluate the effectiveness of primary colposcopy in the genitourinary medicine setting by comparing the cervical cytology and punch biopsy results for women identified as having an abnormal cervical transformation zone. METHOD–A retrospective audit of six years' findings in primary colposcopy was carried out. The punch biopsy findings of 1338 women were compared with their last cervical cytology results. A small sample of biopsies were subjected to in situ hybridisation for human papilloma virus types 6, 11, 16, 18 and cytomegalovirus. RESULTS–The tabulated results demonstrated the variability between histology and cytology. This was explored with reference to other studies. The viral typing showed the dominance of low oncogenic risk human papilloma virus types. CONCLUSION–The findings are discussed against the overall concept of sexual health. Primary colposcopy facilitates empowerment of the patient and her partner through the opportunity for demonstration and explanation of disease processes and options for management. Experience and expertise gathered in six years of primary colposcopy confirm the value of primary colposcopy not only in improved diagnosis and management but also in teaching, audit and research.